2014
DOI: 10.1021/am506482q
|View full text |Cite
|
Sign up to set email alerts
|

Decohesion Kinetics in Polymer Organic Solar Cells

Abstract: We investigate the role of molecular weight (MW) of the photoactive polymer poly(3-hexylthiophene) (P3HT) on the temperature-dependent decohesion kinetics of bulk heterojunction (BHJ) organic solar cells (OSCs). The MW of P3HT has been directly correlated to its carrier field effect mobilities and the ambient temperature also affects OSC in-service performance and P3HT arrangement within the BHJ layer. Under inert conditions, time-dependent decohesion readily occurs within the BHJ layer at loads well below its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 57 publications
2
48
0
Order By: Relevance
“…Turning to the CPs, we observed a much weaker glass transition both for P3HT and P3(4MP)T, as shown in Figure (b,c), respectively. For P3HT, it features a two‐step transition where the first step with a T g of 11.7 °C (this value shows great agreement the literature reported value of 12–14 °C measured with DSC and DMA …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Turning to the CPs, we observed a much weaker glass transition both for P3HT and P3(4MP)T, as shown in Figure (b,c), respectively. For P3HT, it features a two‐step transition where the first step with a T g of 11.7 °C (this value shows great agreement the literature reported value of 12–14 °C measured with DSC and DMA …”
Section: Resultssupporting
confidence: 90%
“…For P3HT, it features a two-step transition where the first step with a T g of 11.7 C (this value shows great agreement the literature reported value of 12-14 C measured with DSC and DMA. 15,[38][39][40][41] ) is associated with the mobile amorphous fraction and the second one with a T g of 42.2 C is related to the rigid amorphous fraction. This is consistent with previous work by Remy et al 42 Upon tuning the side chain isomerism, surprisingly, P3(4MP)T only gives a one-step transition with a T g of 35.2 C. Such a difference is presumably related to the difference in crystalline morphology and requires further investigation in future.…”
Section: Resultsmentioning
confidence: 99%
“…More robust charge transport layers or replacements must be developed that are not mechanically fragile, hydroscopic, corrosive, or susceptible to delamination from perovskite surfaces.Currently, the most efficient perovskite solar cells utilize organic layers to mediate carrier extraction and charge transport [18]. This places perovskite cells in a similar realm as organicbulk heterojunction solar cells, which, when subjected to thermomechanical analysis, both delaminated readily and exhibited poor layer cohesion [19][20][21][22]. …”
mentioning
confidence: 99%
“…The peak fitting results of the O 1s and U 4f were shown in Table 4. Because XPS is not a quantitative analysis method, these data could be used for semiquantitative analysis of the distribution of multicomponent [31,32]. As shown in Figure 6(a), it was observed that complexes 1-3 presented six main components O 1s spectra for oxygen functionalities.…”
Section: Xps Spectra Analysismentioning
confidence: 99%